Encouraging Collaborative Governance in Badan Usaha Milik Desa (BUM Desa) Management in Indonesia - Chandra Wijaya; Vicky Dian Pratama Sari (Program Pascasarjana Universitas Negeri Makassar, 2019)
This essay tries to explore and develop a collaborative governance concept as an alternative approach for developing BUM Desa program of the Ministry of Village, Development Regions and Transmigration. Recently, there are more than 45,000 units of BUM Desa in which 66% of them were established after 2015. However, the vast majority of them are still under-developed. This study uses a qualitative evaluation method for a deeper and more detailed understanding the dynamics of an ongoing program. Data collection techniques used in this study are in-depth interview, Focus Group Discussion (FGD), observation, documentary, visual material and online data gathering with constant comparative analysis. The result from this study explain that ‘BUM Desa Bersama Program’ is an example of a collaborative governance concept. ‘BUM Desa Bersama’ is a collaboration between village’s economic institutions involving several BUM Desa’s across villages. The government needs to encourage broader partnerships to enable experiences exchange which may strengthen the BUM Desa and expand their business scale and market penetration. This partnerships may involve collaboration with public institutions and private institutions.